Power sector benefits of flexible heat pumps in 2030 scenarios - Alexander Roth; Carlos Gaete-Morales; Dana Kirchem; Wolf-Peter Schill (Communications Earth & Environment)
Abstract Heat pumps play a major role in decreasing fossil fuel use in heating. They increase electricity demand, but could also foster the system integration of variable renewable energy sources. We analyze three scenarios for expanding decentralized heat pumps in Germany by 2030, focusing on the role of buffer heat storage. Using an open-source power sector model, we assess costs, capacity investments, and emissions effects. We find that investments in solar photovoltaics can cost-effectively accompany the roll-out of heat pumps in case wind power expansion potentials are limited. Results further show that short-duration heat storage substantially reduces the need for firm capacity and battery storage. Larger heat storage sizes do not substantially change the results. Increasing the number of heat pumps from 1.7 to 10 million units could annually save more than half of Germany’s private and commercial natural gas consumption and around half of households’ building-related CO2 emissions.